Comparison of conventional ICSI and rescue ICSI in patients without severe male factor and poor oocyte yield - Li, Mingzhao; Chen, Wennan; Xue, Xia (Frontiers in Endocrinology, 2025)
ObjectiveThe aim of this study was to explore the effectivity and safety of early rescue intracytoplasmic sperm injection (R-ICSI) in patients with poor oocyte yield and non-severe male factor.MethodsThis study was a retrospective cohort analysis which included 604 conventional ICSI cycles and 116 early R-ICSI cycles at the Northwest Women’s and Children’s Hospital from February 2014 to December 2023. All patients were during their first assisted reproductive technologies (ART) cycle with 3–5 retrieved oocytes. The male partner had normal or mildly impaired sperm parameters. We compared the reproductive outcomes of conventional ICSI and early R-ICSI cycles in such patients.ResultsWe observed that there were no significant differences in the MII (86.75 versus 85.09%; p = 0.329) and two pronuclei (2PN) (71.82 versus 72.02%; p = 0.934) rates between conventional intracytoplasmic sperm injection (ICSI) and early R-ICSI groups. Following conventional ICSI, a total multi-pronuclei (MPN) rate of 1.02% was achieved, which was significantly lower than that of 6.33% after early R-ICSI (p < 0.001). There were no significant differences in the D3 good quality embryo (51.80 versus 49.67%; p = 0.499), D3 available embryo (82.28 versus 78.38%; p = 0.112) and blastocyst formation (65.15 versus 68.69%; p = 0.494) rates between the two groups. We also observed that there were no significant differences in the pregnancy (55.45 versus 50.50%; p = 0.357), clinical pregnancy (52.00 versus 46.53%; p = 0.312), ongoing pregnancy (44.91 versus 39.60%; p = 0.324) and live birth (42.73 versus 37.62%; p = 0.339) rates between the two groups.ConclusionsDespite the higher MPN rate, comparable outcomes can be achieved following early R-ICSI when compared to conventional ICSI for couples with non-severe male factor and poor oocyte yield.